Control Power in Continuous Variable Controlled Quantum Teleportation - Yuehan Tian; Dunbo Cai; Nengfei Gong; Yining Li; Ling Qian; Runqing Zhang; Zhiguo Huang; Tiejun Wang (Entropy)
Controlled quantum teleportation is an important extension of multipartite quantum teleportation, which plays an indispensable role in building quantum networks. Compared with discrete variable counterparts, continuous variable controlled quantum teleportation can generate entanglement deterministically and exhibit higher superiority of the supervisor’s authority. Here, we define a measure to quantify the control power in continuous variable controlled quantum teleportation via Greenberger–Horne–Zeilinger-type entangled coherent state channels. Our results show that control power in continuous variable controlled quantum teleportation increases with the mean photon number of coherent states. Its upper bound is 1/2, which exceeds the upper bound in discrete variable controlled quantum teleportation (1/3). The robustness of the protocol is analyzed with photon absorption. The results show that the improving ability of the control power will descend by the increasing photon loss, with the upper bound unchanged and robust. Our results illuminate the role of control power in multipartite continuous variable quantum information processing and provide a criterion for evaluating the quality of quantum communication networks.